(untitled) (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
It proposes preventative duties for international organizations in the era of COP-30, arguing that the absence of equitable political participation constitutes a form of structural climate injustice that needs to be combated. (Received: September 2025 | Accepted: November 2025)